Phased Array Feeds for the Square Kilometre Array - Van Cappellen, W.; De Vaate, J.; Warnick, K.; Veidt, B.; Gough, R.; Jackson, Carole; Roddis, N. (Institute of Electrical and Electronics Engineers ( IEEE ), 2011)
A novel method to form multiple instantaneous beams on the sky with a reflector antenna is to employ a dense Phased Array Feed (PAF). This technology is currently being developed to greatly increase the survey speed of existing and future radio telescopes. This paper reviews the current state of PAF development projects for radio astronomy, the particular challenges and the potential for incorporation of PAFs into the ultimate radio survey instrument - the Square Kilometre Array.